Limited hydraulic recovery in seedlings of six tree species with contrasting leaf habits in subtropical China - Duan, Honglang; Wang, Defu; Zhao, Nan; Huang, Guomin; Resco de Dios, Víctor; Tissue, David T. (Frontiers in Plant Science, 2022)
Subtropical tree species may experience severe drought stress due to variable rainfall under future climates. However, the capacity to restore hydraulic function post-drought might differ among co-occurring species with contrasting leaf habits (e.g. evergreen and deciduous) and have implications for future forest composition. Moreover, the links between hydraulic recovery and physiological and morphological traits related to water-carbon availability are still not well understood. Here, potted seedlings of six tree species (four evergreen and two deciduous) were grown outdoors under a rain-out shelter. They grew under favorable water conditions until they were experimentally subjected to a soil water deficit leading to losses of ca. 50 % of hydraulic conductivity, and then soils were re-watered to field capacity. Traits related to carbon and water relations were measured. There were differences in drought responses and recovery between species, but not as a function of evergreen or deciduous groups. Sapindus mukorossi exhibited the most rapid drought response, which was associated with a suite of physiological and morphological traits (larger plant size, the lowest hydraulic capacitance (Cbranch), higher minimum conductance (gmin) and lower HV (Huber value)). Upon re-watering, xylem water potential exhibited fast recovery in 1-3 d among species, while photosynthesis at saturating light (Asat) and stomatal conductance (gs) recovery lagged behind water potential recovery depending on species, with gs recovery being more delayed than Asat in most species. Furthermore, none of the six species exhibited significant hydraulic recovery during the 7 d re-watering period, indicating that xylem refilling was apparently limited; in addition, NSC availability had a minimal role in facilitating hydraulic recovery. Collectively, the decoupling of drought recovery in hydraulic and carbon processes may limit water supply to sustain carbon assimilation of seedlings in the longer term, potentially altering seedling regeneration and shifting forest species composition in subtropical China under climate change.